Learner collaboration in a multilevel refugee-background classroom - Marderness, Emily (LESLLA Symposium Proceedings, 2020)
When refugees come together in a classroom to learn a new language, they bring vastly different backgrounds in formal, school-based educational settings. Some are emergent readers learning foundational skills, while other have higher levels of literacy in other languages. Meeting the needs of learners with widely different experiences is key. The teaching context for this paper is a refugee education program at a community college. Two activities are presented that have led to success in meeting different needs in a multilevel English classroom. One activity is creating a graph as a whole class and the other is telling a story in pairs. Experience-based reflections are shared to demonstrate how activities are implemented and how learners responded in this class. Adding to the growing bank or resources for teaching people who are learning to read and write for the first time in a new language, this exploration of activities is applicable to any context with a diverse group of language learners.